An Assessment of the Implementation of the Convention on International Trade in Endangered Species of Wild Fauna and Flora in Kenya - Nicholus Kilonzo; Joel T. Heinen; Patrick Byakagaba (Diversity, 2024)
International trade is hastening extinction for many species of plants and animals despite the fact that many countries have ratified CITES. The adoption of treaties is often symbolic as many countries, especially in the developing world where most biodiversity is found, experience a lack of fit between international agreements and national laws and institutions. Our main objective here is to assess the extent of jurisdictional and institutional fit in the implementation of CITES in Kenya, an important issue given the amount of international trade in wild products and the importance of wildlife tourism to the country. The specific objectives are to assess the following: the capacity and level of coordination among state actors and conservation mandates in national policy and law using a mixed methods approach involving a literature review and 38 key informant surveys representing professional expertise from various stakeholder groups. We found that over 60% of respondents indicated only moderate capacity for the implementation of CITES and coordination between local and central governments. Some participants indicated that judicial officers lack adequate conservation knowledge, thus hampering enforcement via low prosecution rates. A moderate (at best) structural fit involving inefficiencies such as conflicting processes, unequal enforcement, and suboptimal coordination implies a degree of failure in developing the implementation capacity of CITES within Kenya. Our results also show a mismatch between agency staffing and workload at several levels of government, and we make suggestions for improvement.